Long-Term Prognostication for 20 114 Women With Small and Node-Negative Breast Cancer (T1abN0). Issue 1 (26th September 2020) - Jaraj, David; Höijer, Jonas; Widman, Linnea; Ahlgren, Johan; Arnesson, Lars-Gunnar; Einbeigi, Zakaria; Klintman, Marie; Vikhe Patil, Eva; Sund, Malin; Fredriksson, Irma; Bergh, Jonas; Andreas, Pettersson
Abstract: Background: Although small, node-negative breast cancer (ie, T1abN0) constitutes 20% of all newly diagnosed breast cancers, data on prognosis and prognostic factors are limited. Methods: We conducted a population-based cohort study including 20 114 Swedish women treated for T1abN0 breast cancer from 1977 onward. Patient and tumor data were collected from Swedish breast cancer registries. Cohort subjects were followed through linkage to the Cause of Death Register. We calculated the cumulative incidence of breast cancer–specific and overall death and used Cox regression to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: During a median follow-up of 9.1 years (range = 0-38), 915 women died of breast cancer and 5416 of any cause. The 10-, 20-, and 30-year cumulative incidences of breast cancer death were 3.4% (95% CI = 3.1% to 3.7%), 7.6% (95% CI = 7.1% to 8.2%), and 10.5% (95% CI = 9.6% to 11.4%), respectively. The multivariable hazard ratios and 95% confidence intervals of breast cancer death were 0.92 (95% CI = 0.88 to 0.97) for each additional calendar year of diagnosis, 4.38 (95% CI = 2.79 to 6.87) for grade 3 vs grade 1 tumors, 0.43 (95% CI = 0.31 to 0.62) for progesterone receptor–positive vs progesterone receptor–negative disease, and 2.01 (95% CI = 0.99 to 4.07) for HER2-positive vs HER2-negative disease. Women with grade 3 vs grade 1 tumors had a 56% increased risk of death from any cause (HR = 1.56, 95% CI = 1.30 to 1.88). Conclusions: The risk of breast cancer death in T1abN0 disease continues to increase steadily beyond 10 years after diagnosis, has improved over time, and varies substantially by tumor characteristics.